Dampak Pengangkatan Anggota TNI Aktif Sebagai Pejabat Kepala Daerah Terhadap Tatakelola Pemerintah - Ganis Khoirun Nisa; Ahmad Sholikhin Ruslie (Journal Evidence Of Law, 2025)
Regional head officials are people chosen to carry out duties and authority, both at the provincial and city district levels. The appointment of regional head officials is usually chosen by the central goverment throught the president or minister of home affairs to fill vacancies due to the end of their term of office or if the previous official has died. According to law number 10 of 2016 concerning regional elections, the appointment of regional head officials is carried out through an election process by the community. However, in the event of a vacancy, the minister of home affairs has the right to appoint a temporary official to replace the position of the previous official. The filling in of regional head officials refers to artickel 86 of 2014 concerning regional government. The filling of regional haead officials do not go through a direct election mechanism by the people. This causes political domination and pasrty influence in making decisions. In relation to the decision of the minister of home affairs number 4 of 2023 regarding the appointment of regional head officials from active TNI members which if felt to have caused a lot of controversy which is contrary to the TNI Law. The aim of this research is to find out about the appointment af regional head officials according to the government of the minister of home affairs number 4 of 2023. The method used in this writing is normative by taking a case, conceptual and statutory approach. The result and discussion obtained were a legal review of the mechanism for regional head officials according to minister of home affairs regulation number 4 of 2023 article 3 paragraph (b) with the TNI Law article 47 paragraph (1) which contradicts and creates conflicting norms regarding the appointment of public officials from the military.